Changes and continuities in traditional matrimonial alliances in Mithila: The case of Saurath Sabha - Singh, Sugandh (National Geographical Journal of India, 2021)
Saurath village located in Madhubani district, Bihar hosts an annual matrimonial gathering every year and is known for being the centre for the solemnization of marriage. This paper is an attempt to understand the origin of this practice, the temporal change in choices of the stakeholders, the spatial and temporal change in participation in the gathering, and the scope to improve and upgrade the present condition. This paper describes the change in the role of genealogists (Panjikar) in Maithil matrimony, the change in methods of marriage and mate selection. Additionally, the opinion on the revival of Saurath Sabha has been presented. The present study is based on focus group analysis, eld observation and interviews. The road map has been prepared based on SWOTanalysis for presenting suggestions and prospects.